Carbon budgets of coral reef ecosystems in the South China Sea - Yan, Hongqiang; Shi, Qi; Xu, Lijia; Zhang, Huiling; Zhao, Meixia; Tao, Shichen (Frontiers in Marine Science, 2024)
The coral reef ecosystem is one of the most productive ecosystems in the ocean, and is also an important calcium carbonate deposition region. Because excess production is very low in coral reefs, organic carbon reservoirs are very limited. During the calcification process, each mole of CaCO3 will produce 1 mol of CO2, approximately 60% of which will be released into the atmosphere through the sea-air interface. This causes coral reefs to be large inorganic carbon reservoirs, but at the same time, most coral reefs act as atmospheric CO2 sources (which also act as sinks in some coral reefs). Therefore, clarifying the sea-air CO2 exchange flux and carbon storage is critical for understanding the carbon cycle in coral reef ecosystems. In this paper, we summarize the carbon cycle processes in the coral reefs of the South China Sea (SCS) and estimate the total CO2 budget and carbon reserves. According to current research, the coral reefs in this area act as a source of atmospheric CO2, releasing 0.37−1.59 × 1011 g C a-1 into the atmosphere. Owing to their extremely high biological productivity and carbonate productivity, the carbon reserves of coral reefs in the SCS range from 1.66–3.78 × 1012 g C a-1, which is an order of magnitude greater than the CO2 emissions at the sea–air interface. Overall, coral reefs in the SCS are important carbon storage areas. As the current results are still approximate, a more comprehensive and in-depth investigation is needed to clarify the carbon source/sink processes, regulatory mechanisms, and carbon storage capacity of SCS coral reefs.